Organizational Culture, Emotional Intelligence and Motivation: Its Effect on Organizational Citizenship Behavior (OCB) on Employees of State-Owned Enterprises in Indonesia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
State-Owned Enterprises under the Ministry of State-Owned Enterprises of the Republic of Indonesia is finding cases of corruption because of the behavior of employees who are not responsible, so that the Ministry of State Enterprises of the Republic of Indonesia estabished new core values on the organizational culture or all State-Owned Companies. The purpose of this research was to examine the influence of organizational culture, emotional intelligence, and motivation on organizational citizenship behavior (OCB) on employees of State-Owned Enterprises in Indonesia. Researcher set organizational culture, emotional intelligence, and motivation as the independent variable, and organizational citizenship behavior (OCB) as the dependent variable. This research is an exploratory research that proves the causal relationship between the independent variables and the dependent variable using   multiple regression analysis. The results of this research are that together organizational culture, emotional intelligence, and motivation have a considerable influence on organizational citizenship behavior (OCB). Whereas partially, organizational culture has no significant effect on organizational citizenship behavior (OCB) and for emotional intelligence and motivation has a positive and significant effect on organizational citizenship behavior (OCB) on employees in State-Owned Enterprises in Indonesia .